Transport management practices and performance of diamond mining companies in Zimbabwe - James Kanyepe (Cogent Business & Management, 2023)
The purpose of the study is to establish the effect of transport management practices on the performance of diamond mining companies. The study population was comprised of four authorized diamond mining companies in Zimbabwe. The sample size was comprised of 92 respondents drawn from logistics, procurement, and finance departments. Respondents were selected using stratified random sampling techniques. Data was collected using a structured 5-point Likert scale questionnaire. Regression analysis was used to test the relationship between study variables. The study found that vehicle scheduling, route planning, vehicle tracking, and fuel management positively influence the performance of diamond mining companies. This implies that the continued use of inefficient transport management practices has resulted in high transport costs, an increase in greenhouse gas emissions, and lower productivity. The study, therefore, recommended that diamond mining firms adopt contemporary transport technologies and implement safety measures such as regular vehicle maintenance, driver safety checks, and driver training. Furthermore, the study contributes to the existing body of literature on transport management and performance.
Keywords: 650; Fuel Management; Performance; Route Planning; Vehicle Scheduling; Vehicle Tracking